Statistical Comparison of Gravity Wave Characteristics Obtained from Airglow All-Sky Observation at Mt. Bohyun, Korea and Shigaraki, Japan - Tae-Yong Yang; Young-Sil Kwak; Yong-Ha Kim (Journal of Astronomy and Space Sciences, 2015)
Previously, all-sky airglow images observed at Shigaraki (34.9° N, 136.1° E), Japan, during 2004 and 2005 were analyzed in relation to those observed at Mt. Bohyun (36.2° N, 128.9° E) for a comparison of their gravity wave characteristics (Kim et al. 2010). By applying the same selection criteria of waves and cloud coverages as in the case of Mt. Bohyun all-sky images, we derived apparent wavelengths, periods, phase velocities, and monthly occurrence rates of gravity waves at Shigaraki in this study. The distributions of wavelengths, periods, and speeds derived for Shigaraki were found to be roughly similar to those for Mt. Bohyun. However, the overall occurrence rates of gravity waves at Shigaraki were 36% and 34% for OI 557.7 nm and OH Meinel band airglow layers, respectively, which were significantly higher than those at Mt. Bohyun. The monthly occurrence rates did not show minima near equinox months, unlike those for Mt. Bohyun. Furthermore, the seasonal preferential directions that were clearly apparent for Mt. Bohyun were not seen in the wave propagation trends for Shigaraki. These differences between the two sites imply different origins of the gravity waves near the Korean peninsula and the Japanese islands. The gravity waves over the Japanese islands may originate from sources at various altitudes; therefore, wind filtering may not be effective in causing any seasonal preferential directions in the waves in the airglow layers. Our analysis of the Shigaraki data supports recent theoretical studies, according to which gravity waves can be generated from in situ sources, such as mesosphere wind shear or secondary wave formation, in the mesosphere.